The Impact of Local Road Infrastructure on Driver Safety: A Systematic Literature Review - Hartati, Noviar Dwi; Puspitasari, Nina Ripka; Muizz, Fikri Abdul; Rijaluddin , Arief; Taufik, Mohamad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Although human movement and economic growth depend on adequate road infrastructure, unsafe construction can have a detrimental effect on safety. Road crashes, a major global public health issue, necessitate research into multifactorial causes, including driver behavior, vehicle performance, and infrastructure. This study employs a Systematic Literature Review (SLR) to identify key infrastructure factors affecting safety, assess research consistency, and pinpoint knowledge gaps. Using Google Scholar, Publish or Perish, and VOSviewer, secondary data from scientific journals (2000-2025) were analyzed. Results indicate "Artificial Intelligence" (401 occurrences) and "Infrastructure" (129 occurrences) as the most frequent keywords, underscoring a strong interest in leveraging advanced technology for road design and safety. VOSviewer identified eight keyword clusters, with "Learning" (147) and "Road" (98) also prominent. Despite increased research, gaps remain in longitudinal studies for long-term benefits and localized infrastructure adaptation. Future research should adopt a multidisciplinary approach, integrating sociology, environmental science, and advanced technologies like adaptive traffic management and computerized ticketing, to holistically enhance road safety.